IMPACT OF RAPID URBANIZATION ON ENVIRONMENTAL QUALITY IN YENAGOA METROPOLIS, BAYELSA STATE-NIGERIA - Iyorakpo, Julius (European Scientific Journal, ESJ, 2015)
In the event of the creation of Bayelsa State with Yenagoa as capital in 1996, there has been a significant surge of population into the capital territory of the State which is the only location where employment opportunities are available. The rate of rural-urban migration seems to outpace the rate at which planned development is going on. The rate of rapid urbanization taking place in the metropolis of the state capital has led to the emergence of several unplanned structures, haphazard disposition of refuse, lack of drainages, inadequate housing facilities, among others have culminated to poor environmental quality. The goal of this study is to determine the relationship between the impact of rapid urbanization and environmental quality of Yenagoa and its metropolis. In order to achieve the goal of this study, the following hypotheses were formulated for validation as follows: that there is no significant relationship between rapid urbanization and environmental quality in Yenagoa metropolis. The second hypothesis states that; there are no significant differences on the environmental quality at the various locations in Yenagoa metropolis. Five zones were randomly selected for the study. These were namely; the traditional Yenagoa, Onopa, Kpansia, Biogbolo and Agudama-Epie which are areas known for high population concentration as a result of rapid urbanization. Both secondary and primary data including interviews were collected/conducted and analyzed. Results of the findings show that there are serious abuses and contraventions on the environment which result to poor environmental quality. However, recommendations are proffered to mitigate the identified problems.